2020
DOI: 10.1038/s41598-020-72801-1
|View full text |Cite
|
Sign up to set email alerts
|

Severity assessment in mice subjected to carbon tetrachloride

Abstract: The Directive 2010/63 EU requires classifying burden and severity in all procedures using laboratory animals. This study evaluated the severity of liver fibrosis induction by intraperitoneal carbon tetrachloride (CCl4) injections in mice. 29 male C57BL/6N mice were treated three times per week for 4 weeks with an intraperitoneal injection (50 µl) of either 0.6 ml/kg body weight CCl4-vehicle solution, germ oil (vehicle-control) or handling only. Severity assessment was performed using serum analysis, behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
4
12
0
1
Order By: Relevance
“…This indicates a painful impulse caused by the injection, which lasts over the investigation period of one hour after injection. These ndings are in line with our recently published study on the severity of the CCl 4 model itself 24 , which showed the highest severity of the animals in various clinical and behavioral parameters also during the second week of treatment. In Fig.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This indicates a painful impulse caused by the injection, which lasts over the investigation period of one hour after injection. These ndings are in line with our recently published study on the severity of the CCl 4 model itself 24 , which showed the highest severity of the animals in various clinical and behavioral parameters also during the second week of treatment. In Fig.…”
Section: Discussionsupporting
confidence: 92%
“…However, this habituation effect in the CCl 4 group may be due to the increased liver metabolism in the turnover of toxic CCl 4 with the second week of treatment. These changes in liver metabolism were shown elsewhere by blood analysis in the CCl 4 model 24 .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Ключові слова: L-глутамінова кислота, щурі, кров, CCl 4 , АлАТ, АсАТ Потенційна небезпека для організму ссавців від впливу техногенних чинників зумовлена, зокрема, активацією вільнорадикальних реакцій, виникненням тканинної гіпоксії та порушенням детоксикаційної функції печінки. Тетрахлорметан (CCl 4 ) -токсична органічна речовина штучного походження, добре відома у науковій практиці як модельна сполука для вивчення ураження паренхіматозних клітин печінки [7,10,12,13]. За структурою це хлорований вуглеводень.…”
unclassified